Incremental software architecture : a method for saving failing IT implementations - Bell, Michael, 1957 June 22- (2016)
"This book will depict rare insights into actual failed-to-perform software systems, followed by comprehensive root-cause analyses identifying the reasons for their unsuccessful execution in production. Remedies will be provided that offer strategies to tackle the chief issues. Last, architecture and design best practices will conclude the discussion. The book will assist users to: Mitigate risks of software development projects Increase return on investments (ROI) Provide effective tools to assess technological achievability and viability Introduce software design best practices for enterprise architecture efforts Identify actual software construction value proposition Foster software assets reuse and consolidation Accelerate time-to-market "--
Includes index.
Keywords: Software failures; Evolutionary programming (Computer science); Continuous improvement process; Software architecture; COMPUTERS / Desktop Applications / Project Management Software